2016
DOI: 10.3389/fimmu.2016.00413
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Dysregulated Blood NK Cells in Colorectal Cancer Patients Can Be Activated by Cetuximab Plus IL-2 or IL-15

Abstract: The clinical outcome of colorectal cancer (CRC) is associated with the immune response; thus, these tumors could be responsive to different immune therapy approaches. Natural killer (NK) cells are key antitumor primary effectors that can eliminate CRC cells without prior immunization. We previously determined that NK cells from the local tumor environment of CRC tumors display a profoundly altered phenotype compared with circulating NK cells from healthy donors (HD). In this study, we evaluated peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 56 publications
4
80
0
2
Order By: Relevance
“…Moreover, against H460 and MDA-MB-231, TGF-β1 did not decrease avelumab-mediated ADCC activity. Consistent with our results, some studies also showed that TGF-β1 did not suppress cetuximab-mediated ADCC activity against tumor cells with high-EGFR expression (9, 42). On the contrary, in LNCap, which has low PD-L1 expression, TGF-β1 downregulated avelumab-mediated ADCC activity (0.7-fold) (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, against H460 and MDA-MB-231, TGF-β1 did not decrease avelumab-mediated ADCC activity. Consistent with our results, some studies also showed that TGF-β1 did not suppress cetuximab-mediated ADCC activity against tumor cells with high-EGFR expression (9, 42). On the contrary, in LNCap, which has low PD-L1 expression, TGF-β1 downregulated avelumab-mediated ADCC activity (0.7-fold) (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Intratumoral and peripheral NK cells from cancer patients may display phenotype alterations compared with NK cells from healthy donors (7, 42). Lee, et al, reported that the elevated level of plasma TGF-β1 correlated with low NKG2D expression on human NK cells from cancer patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these data confirmed as it was previously demonstrated that cetuximab treatment could promote the cytotoxic activity of PBMCs and NK cells against tumor cells, which could be the underlying MoA of cetuximab against CRC cells [15]. …”
Section: Resultssupporting
confidence: 87%
“…Studies have demonstrated that downregulation of expression of activating cells and upregulation of expression of inhibitory cells occur in the early stages of CRC [15]. The low functionality of NK cells could prevent NK cells from attacking and eliminating tumor cells in the circulation at early and advanced stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation